Managing Violence in Schools : a Whole-school Approach to Best Practice. - Cowie, Helen (Sage Publications, 2007)
The exposure of children to violence at school is a major concern for educators everywhere and a frequent topic of discussion in the media. This timely text, written by experts in research, practice and training in the field, proposes a whole school approach to reduce the impact of violence on children's development, underpinned by recent research findings. The authors take into account: - the personal characteristics of perpetrators, victims, bystanders - the ethos of the school - the quali.